Plasma testosterone concentration is correlated with circulating immune cell abundance in transgender young people on gender-affirming hormone treatment - White, Alice A.; Pearce, Thomas; Coenen, Isabelle; Bickendorf, Xander; Moore, Julia K.; Strauss, Penelope; Saunders, Liz A.; Chaplyn, Georgia; Siafarikas, Aris; Lin, Ashleigh; French, Martyn; Tjiam, Christian; et al. (Frontiers in Immunology, 2025)
Sex hormones, such as oestrogen and testosterone, display significant immune modulatory properties. This is highly relevant for transgender (trans) people who undergo gender-affirming hormone (GAH) treatment. However, only a limited number of studies have evaluated the immunological impact of GAH treatments, and almost none have assessed the impact in trans young people. Following recruitment to the Gender and IMmunity study (GIM) (n =100), biological samples were collected from trans young people (n = 47) including: trans males (birth-registered females taking testosterone-based GAH) and trans females (birth-registered males taking oestrogen-based GAH). All trans participants had taken GAH for at least 6 months. Samples were also collected from control individuals not taking GAH (n = 53). Immune profiles were evaluated using an 18-colour flow cytometry panel. In addition, the commercially available 37-parameter MaxPar panel was used for analysis of a subset of samples (n = 36) by mass cytometry (CyTOF). Immune cell abundance was compared across experimental groups, and correlated with plasma concentrations of oestradiol and testosterone using multiple regression models. From multiple comparisons analyses grouped by birth-registered sex, several differences were detected in the trans groups compared to control groups, in particular relating to abundance of B and T cell subsets. These differences appeared to be mainly associated with levels of plasma testosterone. The most notable differences were in trans males, who had lower numbers of CD11c+ B cells and higher numbers of CD4+ regulatory T cells (Tregs) compared to control females. Using CyTOF, further analysis of B and T cells subsets revealed the frequency of naïve B cells was higher in trans males compared to control females. This also correlated with testosterone concentration in this group. Differences in the abundance of other T cell subsets were detected in both trans males and trans females, however only a decrease in CD161+ T effector memory cells in trans males, compared to control females, was associated with lower testosterone levels. This cross-sectional observational study of young trans individuals suggests that testosterone treatment may have immune modulatory effects, which should be investigated further, including functional studies. While oestrogen treatment was associated with differences in some immune cells in trans females compared with controls, these were generally not associated with plasma oestradiol levels but rather with testosterone levels. Continued immunological research of young trans individuals taking GAH treatment is crucial for positive long-term health outcomes.